Pulsed Vibro-Acoustic Analysis Technique for Monitoring Bone Health in Preterm Infants: A Pilot Study - Chaudhary, Pradeep Kumar; Gu, Juanjuan; Rosen, David P.; Larson, Nicholas B.; Brumbaugh, Jane E.; Fatemi, Mostafa; Alizad, Azra (IEEE access, 2024)
Despite advances in neonatal care, metabolic bone disease of prematurity (MBDP) remains a common problem in preterm infants. The development of non-invasive and affordable diagnostic approaches can be highly beneficial in the diagnosis and management of preterm infants at risk of MBDP. In this study, we present an ultrasound method called pulsed vibro-acoustic analysis to investigate the progression of bone mineralization in infants over time versus weight and postmenstrual age. The proposed pulsed vibro-acoustic analysis method is used to evaluate the vibrational characteristics of the bone. This method uses the acoustic radiation force of ultrasound to vibrate the bone. The generated acoustic waves are detected using a hydrophone placed on the skin over the tibia. The frequency of vibration and the speeds of received acoustic waves have information regarding the material property of the bone. We examined the feasibility of this method through an in vivo study consisting of 25 preterm and 10 full term infants. The pulsed vibro-acoustic data were acquired longitudinally in preterm infants with multiple visits and at a single visit in full term infants. Speed of sound and mean peak frequency of slow and fast sound waves recorded by hydrophone were used to analyze bone mineralization progress. Linear mixed model was used for statistical analysis in characterizing the mineralization progress in preterm infants compared to data from full term subjects. Significance changes in wave parameters (speed of sound and mean peak frequency) with respect to the postmenstrual age and weight in preterm infants were observed with p-values less than 0.05. Statistical significances in speed of sound measurement for both fast and slow waves were observed between preterm and full term infants, with p-values of <0.01 and 0.02, respectively. The results of this pilot study indicate the potential use of vibro-acoustic analysis for monitoring the progression of bone mineralization in preterm infants.